Auditing the auditors: has the establishment of the audit oversight board affected audit quality? - Ismail, Hashanah; Ung, Chui Theng (EconJournals, 2015)
This paper reports on the results of a research into the relationship between audit quality during the years before and after the incorporation of the Audit Oversight Board (AOB) in Malaysia in 2010. As the AOB only audits auditors of listed companies this study is based on 50 companies’ audited financial statements 2 years before and after AOB was established. A total of 200 firm years were observed. Using reported companies’ earnings to proxy for earnings and audit quality the data collected were analyzed using the modified Jones model for discretionary accruals. The study does find the discretionary accruals to be lower after AOB was established although the change is not significant. Although not significant statistically it evidences that having an independent auditor of the auditors with sanctioning powers does contribute towards greater assurance of audit quality being delivered and that regulation of audit complements the self-regulating regime by the profession for auditors of listed companies in Malaysia.